2019
DOI: 10.1186/s12957-019-1698-1
|View full text |Cite
|
Sign up to set email alerts
|

AV loop free flap: an interdisciplinary approach for perineal and sacral defect reconstruction after radical oncological exenteration and radiation in a colorectal cancer patient

Abstract: Background The free flap transfer of a latissimus dorsi flap (LDF) for the closure of sacral wound defects after pelvic exenteration and radiation therapy offers a successful tool of the plastic surgeon. This case report shows the successful coverage using an upstream arterio-venous (AV) loop in combination with an LDF. Case presentation We describe the case of a patient who underwent a pelvic exenteration and radiation therapy due to a local recurrence of rectal cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 14 publications
0
8
0
2
Order By: Relevance
“…The use of AV grafts to facilitate free tissue applications in head and neck reconstruction has previously been described in the literature 1,4,5,9–11,17 . Creation of an autologous AV loop graft can be the precursor for immediate simultaneous vein grafting or a delayed maturation yielding a true arteriovenous fistula.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of AV grafts to facilitate free tissue applications in head and neck reconstruction has previously been described in the literature 1,4,5,9–11,17 . Creation of an autologous AV loop graft can be the precursor for immediate simultaneous vein grafting or a delayed maturation yielding a true arteriovenous fistula.…”
Section: Discussionmentioning
confidence: 99%
“…The use of vein grafts, often saphenous or cephalic, have been previously described in the literature to facilitate microvascular reconstruction by bridging gaps between the donor and recipient vessels as well as creating alternate vascular conduit from larger bore vessels. 1,3,4,[10][11][12][13][14][15][16][17] When both the artery and the vein require grafting, simultaneous vein grafts can be placed, or an arteriovenous loop can be created for later use following a brief period of maturation. Although the concept has been described previously, larger scale studies specific to the head and neck have yet to be reported.…”
mentioning
confidence: 99%
“…Concerning the commonly used artificial arterio-venous fistulas and the rarely applicable loop-shaped grafts (arterial or venous interposition), failure is still a challenging problem [ 2 , 7 , 8 ]. Arterio-venous interposition grafts can be used in clinical reconstructive microsurgery when proper vessels are not available or long enough in free flap operations [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ]. Loop-shaped arterial grafts can be used as an alternative method for vascular access when Cimino fistula creation is not possible [ 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…4). Freie Lappenplastiken können ebenfalls indiziert sein [12]. In dem zugrundeliegenden Fall mit multiplen Voroperationen sowie einer neoadjuvanten Radiatio kann die Präparation und Darstellung der Anschlussgefäße zu komplikationsreich sein.…”
Section: Introductionunclassified
“…Besonders jedoch in Fällen, in denen es zu einem Verlust von gestielten Lappenplastiken kommt, werden freie Lappenplastiken verwendet. Bei vulnerablen Anschlussgefäßen im bestrahlten Gewebe können AV-Loops eine hilfreiche Möglichkeit sein, die Mikrochirurgie sicherer zu gewährleisten [12].…”
Section: Introductionunclassified